Socio-ecological factors associated with probable depression among pregnant and parenting adolescent girls: findings from a cross-sectional study in Burkina Faso and Malawi - Anthony Idowu Ajayi; Elita Chamdimba; Nathalie Sawadogo; Nyawira Gitahi; Abdoul Moumini Tarnagda; Abdoul Kader Ilboudo; Alister Munthali; Chrissie Thakwalakwa; Emmanuel Oloche Otukpa; Boniface Ayanbekongshie Ushie; Caroline W. Kabiru (BMC, 2023)
Plain English Summary Pregnant and parenting adolescents are at a higher risk of poor mental health. If unaddressed or untreated, the consequences may be dire throughout an individual's life. About one in four girls start childbearing before their 19th birthday in Africa. Most of these pregnancies are unintended or unplanned and occur outside wedlock, bringing untoward disruption to every facet of the girl's life. The burden of early parenthood and the stigma of starting childbearing too early and outside wedlock can affect the mental wellness of girls. Yet only a few studies have focused on understanding the burden and drivers of poor mental health among pregnant and parenting girls. Our study contributes to the research on depression among pregnant and parenting girls, highlighting its burden and individual, family, and community drivers. We conducted this study in Ouagadougou, Burkina Faso, and Blantyre, Malawi, between March and September 2021. A total of 980 and 669 pregnant and parenting girls were recruited into this study in Burkina and Malawi. Our analysis shows that 18.8% and 14.5% of pregnant and parenting girls in Burkina Faso and Malawi, respectively, had probable depression. Depression symptoms was higher when girls were older than 17 years, suffered violence from their partners, their partners denied paternity, received no support from their partners and parents, lived in violent neighborhoods, and had no support system in the community. We conclude that depression is high among pregnant and parenting girls. It necessitates screening them for depression during antenatal and postnatal care visits. To effectively address depression among these girls, interventions must canvass support at the family and community levels.